PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PT. INDOSAT, TBK - Joshephine Pungky. N.S; Sunartiyo (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
Analyze the effect of the current ratio and debt to equity ratio on the stock price of PT. Indosat, Tbk The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The sample used is PT. Indosat, Tbk 2012-2019 period by taking data from PT. Indosat, Tbk and IDX data per quarterly. Partially the current ratio has a positive effect on the stock price of PT. Indosat, Tbk and debt to equity ratio do not have a positive effect on PT. Indosat, Tbk. Simultaneous, the current ratio and debt to equity ratio significantly influence the stock prices of PT. Indosat, Tbk.